Iron Deficiency Anemia in Women. Issue 5 (May 2015) - Friedman, Arnold J.; Shander, Aryeh; Martin, Stephanie R.; Calabrese, Rebecca K.; Ashton, Maria E.; Lew, Indu; Seid, Melvin H.; Goodnough, Lawrence Tim
<x xml:space="preserve">Abstract</x> Introduction Iron deficiency anemia (IDA) remains a widely underdiagnosed and unappreciated women's health issue, affecting women of all ages. Despite the fact that IDA is easily diagnosed and treated, it continues to be a major public health issue. The World Health Organization estimates that 30% of nonpregnant and more than 42% of pregnant women have anemia. Methods A multidisciplinary Group for the Research and Education on Anemia Therapy in Women (GREAT Women II) was formed, sponsored by the Society for the Advancement of Blood Management. The goal was to focus attention on the impact of IDA on women at various stages of life and evaluate and use published literature to provide a simple, evidence-based approach to diagnose and treat IDA. Results The group developed specific recommendations for evaluating and treating IDA in women. Initial diagnosis is defined as hemoglobin less than 12 g/dL in nonpregnant women. A trial of iron therapy (4 weeks) can be considered a first-line diagnostic tool. Alternatively, a low or normal mean corpuscular volume (<100 fL), low serum ferritin (<30 μg/L), and/or low transferrin saturation (transferrin saturation <20%) is sufficient to confirm IDA. If the patient does not fit the diagnosis of IDA or fails to respond to a trial of oral iron, or mean corpuscular volume is elevated, further diagnostic evaluation is needed, including iron studies, B12, folate levels, and renal function tests. If results are not definitive, and IDA persists, a hematology referral is recommended. Conclusion Clinicians should routinely identify and treat IDA, thereby decreasing its negative impact on health and quality of life of women. Target Audience Providers of primary healthcare to women. Learning Objectives After completing this CME activity, the learner will be better able to extend knowledge, increase awareness, and improve treatment of iron deficiency anemia in women; to summarize best practice for the detection and diagnosis of iron deficiency anemia in women; and to institute practical guidelines for the use of intravenous iron in women with iron deficiency.